Potential utility of risk stratification for multicancer screening with liquid biopsy tests - Elle S. Kim; Robert B. Scharpf; Montserrat Garcia-Closas; Kala Visvanathan; Victor E. Velculescu; Nilanjan Chatterjee (npj Precision Oncology, 2023)
Abstract Our proof-of-concept study reveals the potential of risk stratification by the combined effects of age, polygenic risk scores (PRS), and non-genetic risk factors in increasing the risk-benefit balance of rapidly emerging non-invasive multicancer early detection (MCED) liquid biopsy tests. We develop and validate sex-specific pan-cancer risk scores (PCRSs), defined by the combination of body mass index, smoking, family history of cancers, and cancer-specific polygenic risk scores (PRSs), to predict the absolute risk of developing at least one of the many common cancer types. We demonstrate the added value of PRSs in improving the predictive performance of the risk factors only model and project the positive and negative predictive values for two promising multicancer screening tests across risk strata defined by age and PCRS.